2020
DOI: 10.1016/j.ebiom.2019.102625
|View full text |Cite
|
Sign up to set email alerts
|

DuoBody-CD3xCD20 induces potent T-cell-mediated killing of malignant B cells in preclinical models and provides opportunities for subcutaneous dosing

Abstract: Background: DuoBody Ò -CD3xCD20 (GEN3013) is a full-length human IgG1 bispecific antibody (bsAb) recognizing CD3 and CD20, generated by controlled Fab-arm exchange. Its Fc domain was silenced by introduction of mutations L234F L235E D265A. Methods: T-cell activation and T-cell-mediated cytotoxicity were measured by flow cytometry following coculture with tumour cells. Anti-tumour activity of DuoBody-CD3xCD20 was assessed in humanized mouse models in vivo. Non-clinical safety studies were performed in cynomolgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 45 publications
1
110
1
Order By: Relevance
“…There is a situation that the two targets are expressed by a tumor cell and an immune cell, respectively. In this case, CD3-based bispecific antibodies are most common, such as CD3xCD19 [63], CD3xCD20 [64], CD3xBCMA [65], CD3-HAC [66]. Because of the expression of CD3 in T cells, if the structural format is IgG-like, then IgG1 must not be selected.…”
Section: Selection Of Igg Subclasses For Bsabs Respectively Against Omentioning
confidence: 99%
“…There is a situation that the two targets are expressed by a tumor cell and an immune cell, respectively. In this case, CD3-based bispecific antibodies are most common, such as CD3xCD19 [63], CD3xCD20 [64], CD3xBCMA [65], CD3-HAC [66]. Because of the expression of CD3 in T cells, if the structural format is IgG-like, then IgG1 must not be selected.…”
Section: Selection Of Igg Subclasses For Bsabs Respectively Against Omentioning
confidence: 99%
“…Hence, major efforts are devoted to developing efficient chimeric antigen receptors (CARs) and T-cell engagers targeting CD20 5 11 . Epcoritamab (DuoBody®-CD3xCD20, GEN3013) is a novel full-length IgG1 bispecific antibody (bsAb) redirecting CD3 + T-cells to CD20 expressing cells 7 , 12 , 13 . In an initial study, we have shown that epcoritamab induces potent T-cell-mediated cytotoxicity towards B-cell NHL cell lines in vitro and in vivo 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Responses were evaluated over a broad range of dosages with dosagedependent responses seen. With treatment ≥ 80 mg, the GEN3013, a CD20/CD3 BiTe, is an IgG1 antibody that is unique in that it is administered subcutaneously rather than IV [100]. In pre-clinical models, subcutaneous administration demonstrated similar bioavailability and B cell depletion as IV administration, but with lower plasma cytokine levels and was hypothesized to result in less CRS but with the same responses in patients [100].…”
Section: Bite Antibodiesmentioning
confidence: 99%
“…With treatment ≥ 80 mg, the GEN3013, a CD20/CD3 BiTe, is an IgG1 antibody that is unique in that it is administered subcutaneously rather than IV [100]. In pre-clinical models, subcutaneous administration demonstrated similar bioavailability and B cell depletion as IV administration, but with lower plasma cytokine levels and was hypothesized to result in less CRS but with the same responses in patients [100]. The preliminary results of a dose-escalation study on 18 patients with relapsed/refractory NHL (n = 14 with DLBCL), were presented at the 2019 ASH conference [99].…”
Section: Bite Antibodiesmentioning
confidence: 99%